Método de análisis para la comprensión de textos narrativos en estudiantes de la mención de lengua y literatura de la Universidad Nacional de Trujillo - Narváez Tapia, Luis Angel (2016)
In the present investigation it shown that the application of the method of cross-sectional analysis comprehensive understanding of literary narrative texts was achieved significantly in students of the 3rd year of the mention of Language and Literature of Academic and Vocational Secondary School faculty of Education and Communication Sciences of the National University of Trujillo. This method was applied in a sample consisting of 33 students at the end of the investigation, evaluated through a post-test, improved the level of comprehensive understanding of literary narrative, expressed in three levels: literal, inferential and critical. Therefore, executed research concluded that the cross-sectional analysis method significantly influed the comprehensive understanding of narrative literary texts due to the successful interpretation of these texts.